Antibacterial activity of the combination of Mentha spicata and Allium sativum extracts on the growth of Mycobacterium tuberculosis clinical isolates - Yunan Jiwintarum; Maruni Wiwin Diarti; I Gede Angga Adnyana; Hady Anshory (Universitas Islam Indonesia, 2022)
Background: Tuberculosis (TB) is a disease with a high mortality rate in the world, including in Indonesia. In addition, the problem of Mycobacterium tuberculosis resistance to antibiotics is getting higher. Mint leaves and garlic have been shown its the ability to kill M. tuberculosis. However, it has never been studied how the combined effect the M. tuberculosis growth.Objective: The major objective of this study was to investigate the anti-mycobacterial activity of mint leaves-garlic combination to growth inhibition of clinical culture M. tuberculosis.Method: Extraction of mint leaves and garlic was carried out by maceration using ethanol as a solvent. M. tuberculosis cultures were obtained from clinical samples of patients diagnosed with new tuberculosis (TBB) and MDR- tuberculosis (TBB). The growth inhibition activity test was carried out using the agar dilution method on Lowenstein Jensen (LJ) media.Results: Mint and garlic extracts, and their combination can inhibit the growth of M. tuberculosis clinical culture from TBB and TBM patients with minimal inhibitory concentration (MIC) of 3 mg/mL.Conclusion: Mint and garlic extracts, and their combination are effective in inhibiting the growth of M. tuberculosis clinical culture and can be used as an alternative treatment for tuberculosis disease.Keywords: mint leaves (Mentha spicata), garlic (Allium sativum), Mycobacterium tuberculosis, multidrug-resistant (MDR)-Tuberculosis Intisari Latar belakang: Tuberkulosis (TBC) merupakan penyakit dengan tingkat kematian yang tinggi di dunia, termasuk Indonesia. Selain itu, masalah resistensi bakteri terhadap antibiotik semakin tinggi. Daun mint (Mentha spicata) dan bawang putih (Allium sativum) telah terbukti dapat membunuh bakteri M. tuberculosis. Namun belum pernah diteliti bagaimana efek kombinasi keduanya dalam membunuh atau menghambat pertumbuhan bakteri M. tuberculosis. Tujuan: Mengetahui aktivitas kombinasi ekstrak daun mint dan bawang putih dalam menghambat pertumbuhan bakteri M. tuberculosis isolat klinik.Metode: Ekstraksi daun mint dan bawang putih dilakukan secara maserasi menggunakan pelarut ethanol. Bakteri uji M. tuberculosis diperoleh dari sampel klinik pasien terdiagnosis tuberkulosis baru (TBB) dan tuberkulosis multidrug resistant (TBB). Uji aktivitas penghambatan pertumbuhan dilakukan menggunakan metode dilusi padat pada media Lowenstein Jensen (LJ).Hasil: Ekstrak daun mint dan bawang putih serta kombinasi keduanya dapat menghambat pertumbuhan bakteri M. tuberculosis isolat klinik dari pasien TBB maupun TBM dengan konsentrasi terkecil 3 mg/mL.Kesimpulan: Ekstrak daun mint dan bawang putih serta kombinasi keduanya efektif menghambat pertumbuhan bakteri M. tuberculosis isolat klinik dan berpotensi untuk digunakan sebagai alternatif pengobatan tuberkulosis.Kata kunci: daun mint (Mentha spicata), bawang putih (Allium sativum), Mycobacterium tuberculosis, multidrug-resistant (MDR)-TB